A Review on Phytoremediation of Indoor Air Pollution: Exploring the efficacy of phytoremediation in mitigating indoor air pollution (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Air pollution in India is a serious issue with the major sources being fuel wood and biomass burning, fuel adulteration, vehicle emission and traffic congestion. Traditional fuel (fuel wood, crop residue and dung cake) dominates domestic energy use in rural India and accounts for about 90 of the total. In urban areas, the traditional fuel constitutes about 24 of the total. Several physical methods are available for purification of air quality but all are expensive and require special equipment for their function. Planting of tree and shrubs for combating pollution and improvement of environment is a cheap and effective way and well recognized throughout the world.